Trade Liberalization and Economic Growth: A Cross-Country Study using Updated Sachs-Warner Index - Siddika, Rahnuma; Ahmad, Sibbir (Asian Journal of Economic Modelling, 2022)
The relationship between trade liberalization and economic growth is a hotly contested issue. Some studies claim a positive impact while others oppose it. This study uses updated data to generate new evidence for the debate. Using a dynamic panel framework and the Sachs-Warner indicator of liberalization, this study finds that trade liberalization does appear to impact growth. The evidence this study generated points to the advocacy for trade liberalization and extending trade volume supporting the view of classical economists. This study revisits the linkage between trade openness and growth through an updated empirical analysis. This paper presents an updated dataset of openness indicators and trade liberalization dates for countries from 1990 to 2010. It finds new evidence on the time paths of economic growth, physical capital investment, and openness around episodes of trade policy liberalization. Using the updated Sachs-Warner index, the study shows that trade liberalization positively affects economic growth.